Analysis of the effects of oil and fuel type on motorcycle fuel consumption vario 125 CC ESP FI - Firmansyah Arya Pangestu; Yoga Guntur Sampurno; Beni Setya Nugraha (Universitas Negeri Yogyakarta, 2024)
The efficiency of fuel consumption in motorcycles is determined by multiple factors, such as the type of oil and fuel utilized. The careful choice of these two elements is essential for enhancing engine performance and reducing operational expenses. This study examines the impact of various oil and fuel types on the fuel consumption of the Honda Vario 125 cc ESP FI motorcycle, with particular attention to the relationship between engine oil viscosity and fuel quality. The study involved conducting experiments with a range of engine oil combinations, specifically 10W-30 and 20W-40, alongside different fuels like Pertalite and Pertamax, each exhibiting distinct octane ratings and combustion properties. The methodology included systematic and thorough testing in controlled environments, where factors like distance and load were standardized to guarantee precision and consistency. The results indicated clear variations in fuel efficiency among the tested combinations. The application of 10W-30 oil in conjunction with Pertalite fuel resulted in a 0.76% enhancement in efficiency when compared to the use of 20W-40 oil with the same fuel type. In a comparable analysis, 10W-30 oil demonstrated a 3.87% increase in efficiency over 20W-40 oil when used with Pertamax fuel. In the analysis of fuel types, Pertamax demonstrated a 16% increase in efficiency compared to Pertalite when used with 10W-30 oil, and a 12.52% increase in efficiency with 20W-40 oil. The results highlight the benefits associated with the utilization of high-quality, low-viscosity oils and higher-octane fuels in achieving improved fuel economy. In summary, the most effective combination for achieving fuel efficiency and cost savings is the use of 10W-30 oil alongside Pertamax fuel. This pairing is advised for Honda Vario 125 cc ESP FI users aiming for improved performance and lower fuel costs.